is Prevalent in Symptomatic Coronary Atherosclerotic Plaque Samples Obtained From Directional Coronary Atherectomy, but its Quantity is Not Associated With Plaque Instability: An Immunohistochemical and Molecular Study - Tomoyuki Otani; Kensaku Nishihira; Yoshinao Azuma; Atsushi Yamashita; Yoshisato Shibata; Yujiro Asada; Kinta Hatakeyama (SAGE Publishing, 2022)
Aim: To clarify whether there is any association between the extent of Chlamydia pneumoniae (C. pneumoniae ) infection and plaque instability or post-directional coronary atherectomy (DCA) restenosis, we determined the frequency of C. pneumoniae infection and its localization in symptomatic coronary atherosclerotic plaques using specimens obtained from DCA. Methods and results: Immunohistochemistry (IHC) and real-time polymerase chain reaction (RT-PCR) revealed the existence of C. pneumoniae in all 50 specimens of coronary atherosclerotic plaques obtained by DCA. C. pneumoniae -positive cell ratio determined with IHC or copy numbers of C. pneumoniae DNA detected by RT-PCR did not differ significantly between patients with stable angina pectoris and those with acute coronary syndrome (IHC: 16.4 ± 7.6% vs 18.0 ± 7.1%, P = .42; RT-PCR: no. of cases with high copy numbers 12/25 vs 10/25, P = .78), or between patients with subsequent post-DCA restenosis and those without (IHC: 17.1 ± 8.0% vs 18.0 ± 7.4%, P = .74; RT-PCR: 5/12 vs 10/21, P = 1.00). Conclusions: C. pneumoniae was highly prevalent in coronary atherosclerotic plaques of patients who underwent DCA. However, the extent of C. pneumoniae infection in coronary atherosclerotic plaques was not associated with plaque instability or post-DCA restenosis.